Metabolomic Analysis Reveals the Therapeutic Effects of MBT1805, a Novel Pan-Peroxisome Proliferator-Activated Receptor Agonist, on α-Naphthylisothiocyanate-Induced Cholestasis in Mice - Wang, Chang; Peng, Fei; Zhong, Bohua; Shi, Ying; Wang, Xiaomei; Jin, Xueyuan; Niu, Junqi (Frontiers in Pharmacology, 2021)
Background & Aims: Therapeutic drugs that are used to treat cholestatic liver disease are limited; however, the results of clinical trials on primary biliary cholangitis treatment targeting peroxisome proliferator-activated receptors (PPARs) are encouraging. In this study, we aimed to identify the effects of MBT1805, a novel balanced PPARα/γ/δ agonist, on cholestasis induced by α-naphthyl isothiocyanate (ANIT) and elucidate the underlying mechanisms through untargeted and bile acid-targeted metabolomic analysis. Methods: Levels of serum biochemical indicators (transaminase, aspartate transaminase, alkaline phosphatase, and total bilirubin) and liver histopathology were analyzed to evaluate the therapeutic effects of MBT1805 on ANIT-induced cholestasis in C57BL/6 mice. Untargeted and bile acid-targeted metabolomic analysis of liver tissues was performed using ultra-high-performance liquid chromatography-triple quadrupole mass spectrometry. qRT-PCR and western blot analysis were carried out to measure the expression of key enzymes and transporters regulating bile acid synthesis, biotransformation and transport. Results: MBT1805 significantly improved abnormal levels of liver biochemical indicators and gallbladder enlargement induced by ANIT. Histopathological analysis showed that MBT1805 effectively relieved ANIT-induced necrosis, vacuolation, and inflammatory infiltration. Untargeted metabolomic analysis identified 27 metabolites that were involved in the primary biliary acid biosynthesis pathway. In addition, bile acid-targeted metabolomics showed that MBT1805 could alleviate the abnormal bile acid content and composition induced by ANIT. Furthermore, qRT-PCR and western blot results confirmed that MBT1805 could effectively regulate bile acid synthesis, biotransformation and transport which helps relieve cholestasis. Conclusions: MBT1805 is a potential candidate drug for cholestasis, with a balanced PPARα/γ/δ activation effect.